2008
DOI: 10.1007/s11745-008-3158-5
|View full text |Cite
|
Sign up to set email alerts
|

SNPs of the FADS Gene Cluster are Associated with Polyunsaturated Fatty Acids in a Cohort of Patients with Cardiovascular Disease

Abstract: Polymorphisms of the human Delta-5 (FADS1) and Delta-6 (FADS2) desaturase genes have been recently described to be associated with the level of several long-chain n-3 and n-6 polyunsaturated fatty acids (PUFAs) in serum phospholipids. We have genotyped 13 single nucleotide polymorphisms (SNPs) located on the FADS1-FADS2-FADS3 gene cluster (chromosome 11q12-13.1) in 658 Italian adults (78% males; mean age 59.7 +/- 11.1 years) participating in the Verona Heart Project. Polymorphisms and statistically inferred ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
150
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(168 citation statements)
references
References 24 publications
14
150
3
1
Order By: Relevance
“…In addition, glycerophospholipids carrying less than 4 unsaturated bonds in their fatty acid chains are increased in individuals who carry the less efficient variant of FADS1, while sphingomyelins are decreased, suggesting a modification in phosphatidylcholines' homeostasis. These observations not only constituted a full replication of the association of this locus with arachidonic acid metabolism as previously reported (Schaeffer et al 2006;Malerba et al 2008), but also underpinned changes in the efficiency of the delta-5 desaturase reaction. This study further demonstrated that metabolic phenotype characterization can be improved by the use of ratios of metabolite concentrations.…”
Section: Targeted Metabolomic Phenotypes In Gwassupporting
confidence: 80%
“…In addition, glycerophospholipids carrying less than 4 unsaturated bonds in their fatty acid chains are increased in individuals who carry the less efficient variant of FADS1, while sphingomyelins are decreased, suggesting a modification in phosphatidylcholines' homeostasis. These observations not only constituted a full replication of the association of this locus with arachidonic acid metabolism as previously reported (Schaeffer et al 2006;Malerba et al 2008), but also underpinned changes in the efficiency of the delta-5 desaturase reaction. This study further demonstrated that metabolic phenotype characterization can be improved by the use of ratios of metabolite concentrations.…”
Section: Targeted Metabolomic Phenotypes In Gwassupporting
confidence: 80%
“…In the Doetinchem Cohort Study, it was concluded that dietary intakes of n-3 and n-6 PUFA interact with FADS1 polymorphism to affect plasma total and HDL-cholesterol levels 166 . In populations consuming a Western diet, it has been shown that the FADS polymorphism which is associated with higher desaturase activity may result in higher risk of proinflammatory response, and thus, atherosclerosis 167,168 . Also, carriers of the rare allele of FADS SNP and their haplotypes had altered eicosanoid precursor levels and a lower prevalence of allergic disease and topical eczema 169 .…”
Section: Fatty Acid Pathophysiology and Gene Interactionsmentioning
confidence: 99%
“…The hypothesis that they play a key role in inflammatory diseases is strengthened by functional studies in mice, where selective D5D and D6D inhibitors showed an anti-inflammatory response. Several single nucleotide polymorphisms (SNP) in FADS genes were reported in humans, and some showed association between FADS SNPs and fatty acids in serum or plasma phospholipids, and erythrocyte membrane and adipose tissue (Schaeffer et al 2006, Malerba et al 2008, Rzehak et al 2009), demonstrating that these concentrations are influenced not only by diet, but also to a large extent by genetic variants common in the world population (Koletzko et al 2011).…”
Section: Polymorphismsmentioning
confidence: 99%